D-dimer measurements in acute aortic dissection - Vladyslava Bazylevska; Alvaro Rosales; Scott Shurmur (Southwest Respiratory and Critical Care Chronicles, 2016)
Acute aortic dissection (AAD) is a medical emergency with significant morbidity and mortality. The diagnosis can be challenging due to the wide array of presenting symptoms and a broad differential diagnosis. Computed tomographic angiography is currently the gold standard for diagnosis of AAD. However, it carries the risk of contrast and radiation exposure and has a financial burden for patients. Multiple biomarkers have been evaluated as a screening tool for AAD. D-dimer has previously been suggested as a sole rule-out test for AAD. It is rapid and inexpensive, is widely available in the emergency rooms, and is highly sensitive for any thrombotic event. This review article evaluates the evidence for the use of D-dimer assays in the diagnosis of AAD, in differentiation of AAD from acute coronary syndromes, and in risk stratification of AAD patients.